Effect of Saccharomyces Boulardii Cell Wall Extracts on Colon Cancer Prevention in Male F344 Rats Treated with 1, 2-Dimethylhydrazine. (19th May 2018) - Fortin, Olivier; Aguilar-Uscanga, Blanca R.; Vu, Khanh D.; Salmieri, Stephane; Lacroix, Monique
ABSTRACT: The effect of Saccharomyces boulardii cell wall extracts on colon cancer prevention in rats treated with 1, 2-dimethylhydrazine was investigated. A crude insoluble glucan (0.5 and 1.0 mg/kg/day) and a crude mannoprotein extract (0.3 and 3.0 mg/kg/day) were administered in rats by gavage for 12 weeks along with a high fat low fiber diet whereupon rats were sacrificed and aberrant crypt foci (ACF) were counted in the colon. Moreover, NAD(P)H: quinone reductase (QR) and harmful fecal enzymes (β-glucosidase and β-glucuronidase) were quantified in the liver and in the caecum, respectively. Results showed a reduction in ACF counts, a decreased β-glucuronidase activity and an increased QR activity when rats were treated only with insoluble glucan. While these enzymatic modulations may be constituted one of the mechanisms that is responsible for the reduction of ACF counts observed, the reduction of ACF counts caused by insoluble glucan should be addressed, at least, as a biomarker of their cancer-prevention properties. To our knowledge, this is the first study demonstrated that crude cell wall extract obtained from S. boulardii could have a potential role in colon cancer prevention in vivo by revealing the potential implication of QR and β-glucuronidase modulation.